Anxiety and depression among care givers of cancer patients in a cancer hospital. - Bhusal,Sumnima (2017)
ABSTRACT; With the increment in the population of cancer patient, the burden associated with caregiving among the family members is increasing simultaneously. The complexity and uniqueness of the care giving to cancer patients varies depending on the type of cancer. Caregivers of cancer patient are at increased risk of psychological problem among which anxiety and depression is considered as major problem. So, the purpose of this study was to find out the anxiety and depression among caregivers of cancer patients. It was descriptive cross sectional study. Non-probability purposive sampling technique was used to collect data from 104 caregivers of cancer patient. Data was collected in Bhaktapur cancer hospital by face to face interview through use of a structured questionnaire and Hospital Anxiety and Depression scale (HADS). Data analysis was done by descriptive and inferential statistics using statistical package for social sciences (SPSS) version 23. Findings of the study revealed that 27.9% of the respondents had normal level of anxiety and 31.7% had borderline level of anxiety whereas 40.4% had abnormal level of anxiety. Similarly, half of the respondents had normal level of depression and 26.9% had borderline level of depression and remaining 23.1% of the respondents had abnormal level of depression. Anxiety level of respondents had significant association with types of cancer (p=0.038), educational level of caregiver (p=0.001), family income per month (p=0.014) and duration of care (p=0.002). However, level of depression of respondents was significantly associated with educational level of caregiver (p=0.018) and relation with patient (p=0.027). Similarly, significant positive interrelationship was found between anxiety and depression (r=0.65). Caregivers of cancer patient are at high risk for clinical anxiety and depression. Mostly, anxiety and depression of caregiver was affected the factors related to caregivers themselves. So, early screening for the psychological morbidity and psychosocial counselling for the family caregivers should be integrated in oncology clinical practice